Effect of tapering period on plasma hormone concentrations, mood state, and performance of elite male cyclists - Zehsaz, F.; Azarbaijani, M. A.; Farhangimaleki, N. F.; Tiidus, P. (European Journal of Sport Science, 2011)
In this study, we investigated the effect of 1- and 3-week tapering periods on concentrations of plasma testosterone (T), cortisol (C), T/C ratio, mood state, and performance in elite male cyclists. After 8 weeks of progressive training, cyclists were randomly assigned to a control group (n=12) who continued performing intense training for a further 3 weeks, or a taper group (n=12) who continued with a 50% reduction in training volume. Blood testosterone and cortisol concentrations were assayed and the T/C ratio calculated from analysis obtained via standard ELISA. Mood state was determined using the Profile of Mood States (POMS) questionnaire. All data were collected immediately after a 40-km time-trial performed before, during, and after the 8-week training protocol and after the 1- and 3-week tapering/training periods. In the taper group, 40-km time-trial time decreased significantly (P<0.01) and equally for both the 1- and 3-week taper periods relative to the control group. There were significant elevations in T/C ratio (P<0.001) and reductions in cortisol concentrations and POMS scores in the taper group relative to the control groups at the end of both the 1- and 3-week tapering periods. Hence, taper periods are effective in improving performance and mood state and elevating the blood T/C ratio.